Can countries lobby for foreign direct investment? : evidence from the US - Montes Rojas, Gabriel Victorio (2018)
This paper empirically studies a mechanism where foreign direct investment (FDI) recipient countries lobby the US government for the allocation of outward US FDI. In this case, lobbying has the goal of informing US policymakers about their countries' market capabilities and of influencing their attitudes toward recipient countries. In turn, policymakers influence firms' decisions about the location of their potential investments abroad.We empirically estimate the direct influence of the recipient country's lobbying agents in obtaining FDI. The econometric results show that increasing foreign lobbying in the US raises the amount of US FDI received. This amount is potentially large for FDI receiving countries.